Contribution of virtual communities to knowledge management in the financial sector - Planuch Prats, Carles; Salvador Vallès, Ramón (Revista General de Información y Documentación, 2022)
In today's digital transformation context, organizations consider knowledge sharing and learning processes increasingly crucial to their success. In this context, information and communication technologies play an important role. In this article the capabilities of virtual communities are analysed in order to be considered a useful tool in knowledge sharing, for innovation, and for the company growth; and we give a range of such examples in the finance sector where information technologies have been used to aide these, with varying degrees of success. This has proven that virtual communities have contributed to the development of numerous products and services according to the needs of customers and to improve good practices in the organization, as well as the training of employees. Creating a favourable context for both clients and employees to participate in the communities by sharing experiences or needs is undoubtedly paramount. And from a technological point of view it seems that Web 2.0 tools are a useful tool to implement these communities in order to improve knowledge management, innovation and results in financial services. This article proposes a conceptual scheme based on the relationship of three research areas, ICT, with special emphasis on Web 2.0 tools, the creation and exchange of knowledge and virtual communities. Data are provided for the three main Spanish financial institutions, that is, Banco Santander, BBVA and CaixaBank. The results obtained show how knowledge is created and shared, based on virtual communities and later adopted in said entities; and that the process of creating and sharing knowledge positively influences entities since: it accelerates the development and implementation of new financial products and services, intensifies the entity's innovation and improves relationships with clients.
Keywords: Knowledge management; Information and communication technologies; financial services; virtual communities